Efficacy of lure mixtures in baited traps to attract different fruit fly species in guava and vegetable fields - Ahmad, Shakil; Jaworski, Coline C.; Ullah, Farman; Jamil, Momana; Badshah, Hayat; Ullah, Farman; Luo, Yanping (Frontiers in Insect Science, 2023)
Fruit flies (Diptera: Tephritidae) are major pests of fruits and vegetables worldwide. We measured the efficacy of attractive lure mixtures in baited traps on naturally-occurring fruit flies in commercial mosaic guava and vegetables fields in Pakistan. We tested three mixtures (methyl-eugenol [ME] and cue lure [CL]; GF-120 and methyl eugenol; and GF-120 and cue lure) in eleven ratios: 0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10, and 100:0. We recorded three fruit fly species: Bactrocera zonata was the most abundant in baited traps, followed by Bactrocera dorsalis, while Zeugodacus cucurbitae was significantly less attracted to baited traps. We also found that the most attractive mixture and ratio varied among species: B. dorsalis was most attracted by 40CL:60ME, while B. zonata was most and equally attracted by 100ME, 10CL:90ME, 20CL:80ME, 30CL:70ME, and 40CL:60ME. Finally, Z. cucurbitae was most attracted by 10CL:90ME, which resulted in the highest total number of flies counted in 10CL:90ME-baited traps. Other mixtures involving GF-120 were less attractive to all three species. Our results suggest that using lure trapping could be an effective alternative to chemical control of fruit flies in crop fields, but that the specific mixture should be adjusted to the main pest target: if Bactrocera species are most damaging and abundant, a 40CL:60ME mixture in baited traps will likely be most effective to reduce pest abundance and crop damage. However, if Z. cucurbitae is the main pest target causing most crop damage and yield loss, 10CL:90ME-baited traps will be a more effective pest control method.